Ketersediaan kedelai di indonesia - , ADNINDITA KUSUMANURENDRANI; , Prof. Dr. Ir. Dwidjono Hadi Darwanto, MS. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aimed to (1) analyze development the availability of soybean in Indonesia, (2) analyze factors that affect availability and demand of soybean in Indonesia, (3) analyze development of dependency soybeans import. This study uses secondary data obtained from the BPS (Badan Pusat Statistik), FAO (Food and Agriculture Organization), World Bank, and Ministry of Finance. In this study, to investigate the availability of soybean development in Indonesia used secondary data span from 1961 to 2010. Availability of soybean development can be observed by means of graphs and trend lines. Data that used to investigate factors that influence the availability and demand for soybean in Indonesia is a secondary data span from 1986 to 2010. To investigate factors that influence the availability and demand for soybeans was used multiple linear regression model. Data that used to investigate the development of import dependence is secondary data span from 1971 to 2010. To investigate the development of soybean import was analyzed by trend analyzed and t test. The result of study showed that availability of soybean and rate dependence soybean imports in Indonesia since 1986 to 2010 has increase. Moreover, the availability of soybean in Indonesia positively influenced by domestic soybean prices, the price of imported soybeans, and soy sauce price. Demand for soybean in Indonesia is influenced positively by domestic soybean prices, the price of imported soybean, and negatively affected by the price of tempe.